Aplikasi JAKI Sebagai Pelayanan Publik dalam Pengelolaan Sampah di Dki Jakarta - Jacky, Jacky; Tjenreng, Muhammad Baharuddin Zubakhrum (Jurnal PKM Manajemen Bisnis, 2025)
This study explores the role of digitalization in improving public services, particularly in waste management in DKI Jakarta. Through an in-depth analysis of the JAKI application and a review of relevant literature, this study identifies the potential and challenges of implementing digitalization in waste management. The results show that digitalization through JAKI has contributed positively to increasing transparency, public participation, and efficiency in waste management. However, there are still a number of challenges such as limited access to technology, slow bureaucratic processes, and low public participation. To overcome these challenges, this study recommends several strategies, such as developing a comprehensive digital platform, training and educating the public, integrating data efficiently, improving technology infrastructure, and partnering with third parties. Thus, it is expected that digitalization can be an effective solution to address waste management problems in DKI Jakarta and improve the quality of life for the community.